Cause of death in people living with HIV who initiated antiretroviral therapy after enrolling to the Thai National AIDS Program from 2008 to 2021Research in context - Cheewanan Lertpiriyasuwat; Stephen J. Kerr; Sairat Noknoy; Patiphak Namahoot; Niramon Punsuwan; Tanakorn Apornpong; Jiratchaya Sophonphan; Napon Hiranburana; Ploenchan Chetchotisakd; Opass Putcharoen; Kiat Ruxrungtham; Anchalee Avihingsanon (The Lancet Regional Health - Southeast Asia)
Summary: Background: Widespread access to antiretroviral therapy (ART) has led to near-normal life expectancies for people living with HIV (PLHIV), shifting the leading cause of death (COD) from AIDS-related to non-AIDS-related mortality. We assessed trends in COD among PLHIV who initiated ART in Thai National AIDS Program (NAP). Methods: We analysed NAP data from PLHIV aged ≥15 at ART initiation, who started ART under Thailand’s universal health coverage from 2008 to 2021. Individual data was linked with the National Death Registration system, and a rule-based algorithm applied text mining to classify COD as AIDS-related, non-AIDS-related and uncertain. Competing risk models examined associations between demographic and clinical characteristics and COD. Standardized mortality ratios (SMR) were calculated using mortality rate from the general Thai population. Findings: Among 398,182 PLHIV (37.1% females) enrolled, the median (IQR) age was 35 (28–43) years, 43.6% commenced ART with CD4 counts <200 cells/mm3. Over 2,631,435 person years of follow-up, 73,768 (18.5%) deaths occurred: 56% AIDS-related, 40% non-AIDS-related and 4% uncertain. The cumulative incidence of AIDS-related mortality at 14 years was 14.74%, non-AIDS-related 12.04% and all-cause mortality 27.93%. AIDS-related deaths declined from 60% to 50% over the study period. Low CD4 counts, permanently loss to care and treatment at non-capital city were significantly associated with higher AIDS-related mortality. The SMR was higher in females [9.08 (95% CI 8.97–9.20] compared to males [5.83 (95% CI 5.78–5.88). Interpretation: AIDS-related mortality decreased over time, but continued efforts are needed to improve earlier diagnosis, and equitable outcomes for women and those residing outside major cities. Funding: Supported by National Institute of Health (IeDEA:U01AI069907).